Efficient Photothermal Anti-/Deicing Enabled by 3D Cu2-x S Encapsulated Phase Change Materials Mixed Superhydrophobic Coatings - Hou, Mingtai (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2023 Wiley-VCH GmbH.